Advanced glycation end product cross-link breaker attenuates diabetes-induced cardiac dysfunction by improving sarcoplasmic reticulum calcium handling - Kranstuber, Allyson; del Rio, Carlos; Biesiadecki, Brandon; Hamlin, Robert; Ottobre, Joseph; Gyorke, Sandor; Lacombe, Véronique A. (Frontiers in Physiology, 2012)
Diabetic heart disease is a distinct clinical entity that can progress to heart failure and sudden death. However, the mechanisms responsible for the alterations in excitation-contraction coupling leading to cardiac dysfunction during diabetes are not well known. Hyperglycemia, the landmark of diabetes, leads to the formation of advanced glycation end products (AGE) on long-lived proteins, including SR Ca2+ regulatory proteins. However, their pathogenic role on SR Ca2+ handling in cardiac myocytes is unknown. Therefore, we investigated whether an AGE cross-link breaker could prevent the alterations in SR Ca2+ cycling that lead to in vivo cardiac dysfunction during diabetes. Streptozotocin-induced diabetic rats were treated with Alagebrium Chloride (ALT-711) for 8 weeks and compared to age-matched placebo-treated diabetic rats and healthy rats. Cardiac function was assessed by echocardiographic examination. Ventricular myocytes were isolated to assess SR Ca2+ cycling by confocal imaging and quantitative Western blots. Diabetes resulted in in vivo cardiac dysfunction and ALT-711 therapy partially alleviated diastolic dysfunction by decreasing isovolumetric relaxation time and myocardial performance index (by 27 and 41% vs. untreated diabetic rats, respectively, P<0.05). In cardiac myocytes, diabetes induced prolongation of cytosolic Ca2+ transient clearance by 43% and decreased SR Ca2+ load by 25% (P<0.05); these parameters were partially improved after ALT-711 therapy. SERCA2a and RyR2 protein expression was significantly decreased in the myocardium of untreated diabetic rats (by 64 and 36% vs. controls, respectively, P<0.05), but preserved in the treated diabetic group compared to controls. Collectively, our result suggest that, in a model of type 1 diabetes, AGE accumulation primarily impairs SR Ca2+ reuptake in cardiac myocytes and that long term treatment with an AGE cross-link breaker partially normalized SR Ca2+ handling and improved diabetic cardiomyopathy.